Comparing Clinical Outcomes After Subacromial Spacer Insertion Versus Other Reconstruction Methods in the Treatment of Irreparable Massive Rotator Cuff Tears. Issue 9 (25th September 2019) - Oh, Joo Han; Park, Joo Hyun; Jeong, Hyeon Jang; Rhee, Sung-Min
Background: Previous studies on subacromial spacer (SAS) insertion have been limited to case series that did not compare the effectiveness of this technique with other techniques. Hypothesis: Outcomes after SAS insertion for the treatment of irreparable massive rotator cuff tears (IMRCTs) will be similar to those of other techniques. Study Design: Cohort study; Level of evidence, 3. Methods: This retrospective study was based on data collected from patients who underwent correction of IMRCTs between January 2010 and October 2017. Group 1 patients (n = 17) received SAS insertion with or without partial repair; group 2 patients (n = 36) were treated with other techniques (isolated partial repairs or bridging grafts). Preoperative tear size and global fatty degeneration index values were evaluated. Range of motion, visual analog scale for pain, American Shoulder and Elbow Surgeons (ASES) score, Constant score, Simple Shoulder Test (SST), Disabilities of the Arm, Shoulder and Hand score, and acromiohumeral distance (AHD) were assessed preoperatively and at final follow-up at least 2 years after the surgery (range, 24-60 months). In both groups, ultrasonographic examination was performed at 3 and 6 months postoperatively, and magnetic resonance imaging (MRI) was performed at 1 year. Results: Tear size and preoperative global fatty degeneration index were not significantly different between the groups (all P > .05). There were no differences in functional scores between the groups at final follow-up (all P > .05). AHD was maintained at final follow-up in group 1 (mean ± SD: 6.2 ± 2.1 mm [postoperatively] vs 6.7 ± 2.3 mm [final follow-up]; P = .678), and there was no difference compared with group 2 (7.2 ± 3.2 mm; P = .244). Patients with retears in group 2 (23 of 36, 63.9%) had lower ASES ( P = .041) and SST ( P = .027) scores at final follow-up when compared with patients in group 1. Six patients (35.3%) in group 1 had partial repairs; these patients had better external rotation at 90° ( P = .047), better SST scores ( P = .036), and higher AHDs at final follow-up ( P = .046) than those in group 1 who had no repair. Three patients (50%) showed retears of partially repaired tendons on MRI. Of 13 patients (76.5%) in group 1 with postoperative MRI, 12 (92.3%) showed fibrotic tissue in the subacromial space not seen preoperatively. Conclusion: There was no difference in outcomes between SAS and the other reconstruction methods for treating IMRCTs. However, given the high retear rate associated with other techniques and poor functional outcomes after retear, SAS insertion could be a viable option for treating IMRCTs.